Short Stories as Indonesian Language Teaching Material for Foreign Students - Sabrina Andin Rakhmawati; Laily Nurlina (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
Indonesian learning material for foreign students is very important especially enriched by local culture. This research discussed about the usage of short stories to introduce some local language (Bali) for readers. The method in this research is qualitative descriptive. The source of data is from novel by title Sagra by Oka Rusmini. The short stories captured Balinese culture in some point of views such as religion, vocabularies , language, and livelihood system. It is very interesting because a lot of people come to Bali as tourists and by the development of this learning material will attract them to learn Indonesian language.